A study on tourists perceived sacrifices at rural destination - Kaur, Jasdeep; Dr Nimit Chowdhary, (IJRDO - Journal of Business Management, 2017)
Rural tourism has gained a sudden prominence in India in the last decade and still much more is left to be explored. The importance of rural tourism as a part of the overall tourism market depends on each country’s tourism resources, infrastructure image, market access and the presence of other types of tourism products. The development of tourism in a rural area is not simply a matter of matching tourist demands with local product supply but a matter of evaluating local suitability and acceptability. Many successful experiences in development countries prove that tourism can become a leading sector for the people who conserve natural resources and live on it. The results of the study reveal that the rural tourism sector has specific characteristics that tourists greatly value and that other specialist tourist markets cannot offer, as highlighted in the contribution made by rural tourism enterprises to rural sustainability. This knowledge can help tailor product development and destination design to suit specific demands of rural tourists and influence communication and promotional activities, hence will try to reduce the level of their sacrifices.